Integrating Technology and Student Learning Independence in Islamic Religious Education - Ida Faridatul Hasanah; Nabilla; Uswatun Hasanah; Sri Suci Suryawati; Sugeng Riyadi (Attanwir : Jurnal Keislaman dan Pendidikan, 2024)
One of the transformations in the field of education includes the rapid development of digital technology. Traditional teaching methods centered on lecturers are considered less effective in meeting the needs of modern students. Technology offers various tools and platforms that can enrich the learning process and support student learning independence. However, the implementation of technology in Islamic religious education still faces various challenges. This research aims to explore new approaches in Islamic religious education through the integration of technology and support for student learning independence. The research methodology used is library research, where data is collected from various written sources such as books, scientific journals, conference papers, theses, and credible online sources. The results of the study show that the integration of technology in Islamic religious education can increase accessibility by providing various learning resources, offering interactive learning, and providing instant feedback. Some identified new approaches include the use of mobile applications, e-learning platforms, social media, and educational games. To improve the quality of Islamic religious education through technology, it is recommended that educational institutions provide training for lecturers, develop a digital curriculum, enhance technological infrastructure, encourage student collaboration, and conduct regular evaluations. Thus, it can be concluded that the integration of technology in Islamic religious education has great potential to support student learning independence. By implementing the identified new approaches, Islamic religious education can become more relevant and effective in the digital era.